Study of Citric Acid-Locust Bean Gum as a Glidant to Fillers of Cellulose Derivatives - Hadinugroho, Wuryanto (Science and Technology Indonesia, 2024)
Citric acid-locust bean gum (CA-LBG) was introduced as an excipient in tablet preparations. CA-LBG is a compound derived from the esterification of citric acid (CA) with locust bean gum (LBG). The experiment aimed to determine the potential and effect of CA-LBG as a glidant on microcrystalline cellulose (MCC). The CA-LBG concentrations in the experiments were 0.5%, 1.0%, 2.0%, and 4.0%. Talc and magnesium stearate (MgS) as a comparison. The mixtures were evaluated for flow rate and angle of repose. The mixture was compressed into tablets weighing 700 mg. Tablets were evaluated for weight, hardness, and friability. The flow rate of the mixture containing CA-LBG 0.5%-4.0% was 12.77 g.sec-1-15.96 g.sec-1. The angle of repose of the mixture containing CA-LBG 0.5%-4.0% is 32.62○-35.52○. The weight of tablets containing CA-LBG 0.5%-4.0% is 700.0 mg-701.2 mg. The hardness of tablets containing CA-LBG 0.5%-4.0% is 6.30 kp-6.90 kp. The friability of tablets containing CA-LBG 0.5%-4.0% is 0.17%-0.36%. The CA-LBG has the potential as a glidant in MCC fillers. Increasing CA-LBG concentration causes the flow rate to increase, the angle of repose to decrease, and the hardness to increase. CA-LBG concentrations of 0.5% and 4.0% reduced tablet friability.